Scope and standards of practice for professional ambulatory care nursing - American Academy of Ambulatory Care Nursing (Pitman, NJ : American Academy of Ambulatory Care Nursing, 2023)
This newly released publication is an updated scope of practice statement and 17 revised standards for the clinical and administrative professional practice of ambulatory care registered nurses (RNs). The standards promote effective clinical and administrative management of increasingly complex ambulatory care RN roles and responsibilities in a changing health care environment. In addition to the revised scope of practice, this publication contains 17 standards. The first six standards address the phases of the nursing process; the last 11 standards address professional performance.These changes offer clarification and specificity for the distinct domains of clinical and administrative nursing practice in ambulatory care settings.
Scope and standards revision task force -- Overview of the AAACN standards 10th edition -- Scope of practice for professional ambulatory care nursing -- Standards of Practice for Professional Ambulatory Care Nursing. Standards of professional clinical practice -- Standards of nursing organizational and professional performance.
Print version record.
Includes bibliographical references (pages 51-53).
WorldCat record variable field(s) change: 050
Keywords: Nursing services -- Administration -- Standards; Ambulatory medical care -- Administration -- Standards; Nursing -- Standards; Ambulatory medical care -- Standards; Ambulatory Care -- standards; Nursing Care -- standards; Clinical Competence -- standards; United States; Services infirmiers -- Administration -- Normes; Traitement ambulatoire -- Administration -- Normes; Soins infirmiers -- Normes; Traitement ambulatoire -- Normes; Ambulatory medical care -- Standards; Nursing services -- Administration -- Standards; Nursing -- Standards; Guideline